Extraction of essential oils from sweet orange and lemongrass, and the development of air fresheners as an approach to experimentation and contextualization in Organic Chemistry education (Research, Society and Development, 2024)
Chemistry is a field of science that studies matter and its interactions with the environment. Some of these concepts can be considered difficult to comprehend for high school students, as subjective ideas are often used to explain some content, like functional groups and carbon chains. Considering this, the purpose of this research is to contextualize the experimental classes of Organic Chemistry with the student's everyday life, aiming to awaken their interest and engagement in the lessons. Based on this objective, a method was planned to associate the content with an easily accessible object for the student, allowing them to visualize, through the object, the subject they learned in the classroom, thus making the learning meaningful. The methodology adopted in this work was a qualitative approach of participant research, where the essential oils of lemongrass (Cymbopogon citratus) and sweet orange (Citrus sinensis) were extracted using the hydrodistillation method to produce air fresheners. The students were able to take these home as a souvenir of the practical class and the reviewed content. As an evaluation of the activity, a questionnaire was administered to assess the students' satisfaction level, gather their opinions on whether they desire more contextualized activities in Chemistry education, and obtain suggestions for improvement. Additionally, they classified the carbon chain and identified the major functional groups present in the essential oils of lemongrass (citral) and sweet orange(limonene). Student’s responses to the questionnaire allowed observation of the knowledge apprehension through the experiments carried out.